False Negative Cell-Free DNA Screening Result in a Newborn with Trisomy 13. (22nd February 2016) - Cao, Yang; Hoppman, Nicole L.; Kerr, Sarah E.; Sattler, Christopher A.; Borowski, Kristi S.; Wick, Myra J.; Highsmith, W. Edward; Aypar, Umut
Abstract : Background. Noninvasive prenatal screening (NIPS) is revolutionizing prenatal screening as a result of its increased sensitivity, specificity. NIPS analyzes cell-free fetal DNA (cffDNA) circulating in maternal plasma to detect fetal chromosome abnormalities. However, cffDNA originates from apoptotic placental trophoblast; therefore cffDNA is not always representative of the fetus. Although the published data for NIPS testing states that the current technique ensures high sensitivity and specificity for aneuploidy detection, false positives are possible due to isolated placental mosaicism, vanishing twin or cotwin demise, and maternal chromosome abnormalities or malignancy. Results. We report a case of false negative cell-free DNA (cfDNA) screening due to fetoplacental mosaicism. An infant male with negative cfDNA screening result was born with multiple congenital abnormalities. Postnatal chromosome and FISH studies on a blood specimen revealed trisomy 13 in 20/20 metaphases and 100% interphase nuclei, respectively. FISH analysis on tissues collected after delivery revealed extraembryonic mosaicism. Conclusions. Extraembryonic tissue mosaicism is likely responsible for the false negative cfDNA screening result. This case illustrates that a negative result does not rule out the possibility of a fetus affected with a trisomy, as cffDNA is derived from the placenta and therefore may not accurately represent the fetal genetic information.